STAT3 Hyperactivation Due to SOCS3 Deletion in Murine Osteocytes Accentuates Responses to Exercise‐ and Load‐Induced Bone Formation - McGregor, Narelle E; Walker, Emma C; Chan, Audrey SM; Poulton, Ingrid J; Cho, Ellie H‐J; Windahl, Sara H; Sims, Natalie A (Journal of bone and mineral research, 2022)
ABSTRACT Cortical bone develops and changes in response to mechanical load, which is sensed by bone‐embedded osteocytes. The bone formation response to load depends on STAT3 intracellular signals, which are upregulated after loading and are subject to negative feedback from Suppressor of Cytokine Signaling 3 (Socs3). Mice with Dmp1Cre‐targeted knockout of Socs3 have elevated STAT3 signaling in osteocytes and display delayed cortical bone maturation characterized by impaired accrual of high‐density lamellar bone. This study aimed to determine whether these mice exhibit an altered response to mechanical load. The approach used was to test both treadmill running and tibial compression in female Dmp1Cre.Socs3f/f mice. Treadmill running for 5 days per week from 6 to 11 weeks of age did not change cortical bone mass in control mice, but further delayed cortical bone maturation in Dmp1Cre.Socs3f/f mice; accrual of high‐density bone was suppressed, and cortical thickness was less than in genetically‐matched sedentary controls. When strain‐matched anabolic tibial loading was tested, both control and Dmp1Cre.Socs3f/f mice exhibited a significantly greater cortical thickness and periosteal perimeter in loaded tibia compared with the contralateral non‐loaded bone. At the site of greatest compressive strain, the loaded Dmp1Cre.Socs3f/f tibias showed a significantly greater response than controls, indicated by a greater increase in cortical thickness. This was due to a greater bone formation response on both periosteal and endocortical surfaces, including formation of abundant woven bone on the periosteum. This suggests a greater sensitivity to mechanical load in Dmp1Cre.Socs3f/f bone. In summary, mice with targeted SOCS3 deletion and immature cortical bone have an exaggerated response to both physiological and experimental mechanical loads. We conclude that there is an optimal level of osteocytic response to mechanical load required for cortical bone maturation and that load‐induced bone formation may be increased by augmenting STAT3 signaling within osteocytes. © 2021 American Society for Bone and Mineral Research (ASBMR).